2002
DOI: 10.1046/j.1365-4362.2002.01630.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DQ3 is associated with idiopathic guttate hypomelanosis, whereas HLA‐DR8 is not, in a group of renal transplant patients

Abstract: The presence of HLA-DQ3 in patients with IGH suggests a genetic basis in a group of renal transplant subjects. HLA-DR8 was found in patients without IGH, and it could play a role as a "protective factor" preventing subjects from developing IGH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
0
9
1
2
Order By: Relevance
“… 10 revealed a highly statistically significant preponderance of manifestations of IGH among the relatives of IGH subjects compared with those of normal controls, which clearly indicated a family aggregation among subjects with IGH. In a group of 22 Columbian renal transplant patients, HLA‐DQ3 was found to be significantly associated with IGH 14 . In this study, only 7% of our patients identified IGH lesions occurring in family members.…”
Section: Discussioncontrasting
confidence: 57%
“… 10 revealed a highly statistically significant preponderance of manifestations of IGH among the relatives of IGH subjects compared with those of normal controls, which clearly indicated a family aggregation among subjects with IGH. In a group of 22 Columbian renal transplant patients, HLA‐DQ3 was found to be significantly associated with IGH 14 . In this study, only 7% of our patients identified IGH lesions occurring in family members.…”
Section: Discussioncontrasting
confidence: 57%
“…The exact mechanism underlying IGH is unclear. Genetic factors such as HLA‐DQ3, chronic sun exposure, trauma, and autoimmunity have been suggested as causative factors 2,3,12–14 . The appearance of small and large leukodermic spots in patients irradiated with high‐intensity UVA and psoralens, over a relatively short period of time, and the finding of IGH lesions on the more exposed areas of the upper and lower extremities, raises the question of a possible role of chronic natural UV light exposure as one of the causative factors 11 .…”
Section: Discussionmentioning
confidence: 99%
“…339,340 Repigmentation does not occur. In a group of renal transplant patients, the presence of this condition correlated with the presence of HLA-DQ3 341. In a group of renal transplant patients, the presence of this condition correlated with the presence of HLA-DQ3 341.…”
mentioning
confidence: 84%